Simulation of undrained quasi-saturated soil with pore pressure measurements using a discrete element (DEM) algorithm - Kuhn, Matthew R.; Daouadji, Ali (Soils and foundations, 2020)
A method is presented for using DEM to find the pore pressure, total stress, and effective stress within a granular assembly during either undrained or drained conditions, by using poroelastic principles to directly determine the pore fluid pressure. The paper considers both the saturated and quasi-saturated conditions, the latter meaning a slightly unsaturated granular material, in which isolated gas bubbles reduce the compressibility of the pore fluid but do not form liquid bridges between the particles. The presence of air increases the pore fluid compressibility and is known to improve undrained strength and liquefaction resistance and has been considered for remediation of loose, susceptible soils. Past DEM studies have approximated undrained loading as a constant-volume condition, but this approximation does not allow the simulation of complex loading sequences, even with fully saturated materials. The paper’s method allows the direct control and measurement of total stress, water pressure, and water influx. The method includes the effects of water compressibility, grain compressibility, pore air compressibility, surface tension, air solubility within the pore liquid, and vapor pressure of the water gas phase. These factors all affect the evolving sizes of the bubbles and the consequent compressibility of the air–water mixture. The resulting algorithm is applied in three examples: the laboratory saturation of a soil specimen by increasing chamber pressure and back pressure, the undrained triaxial compression of quasi-saturated specimens, and the cyclic undrained triaxial liquefaction of quasi-saturated specimens. Example simulations agree favorably with laboratory tests.